Population fluctuation of leafhopper on Bean cultivars in Minas Gerais - Cecília, Lenira Viana Costa Santa; Fátima, Ângela de; Abreu, Barbosa (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this experiment was to study the populational fluctuation of Empoasca kraemeri Ross & Moore 1957 on 18 bean (Phaseolus vulgaris L.) cultivars. The experiment was carried out in three localities of the south region of Minas Gerais, Brazil, in rainy and dry seasons. Insects samplings in nymphal stages were made 20, 48 and 70 days after planting. The results showed that the highest population of nymphal occurred at 70 days after planting except in Lavras (48 days). The highest populational density was observed on Palmital Precoce Cultivar. During the dry period, it was observed that the highest density of pest and the local of the highest incidence was in Careaçu.
Keywords: Phaseolus vulgaris; Empoasca kraemeri